Changes of impact force during performance of straight punch with two boxing techniques - Case study - Dukaric, V.; Ocic, M.; Bon, I.; Rupcic, T.; Knjaz, D. (Studia Sportiva, 2022)
PURPOSE: Performance in boxing is a combination of strength, speed, and stability to create maximum impact. One of the types of punches commonly used in boxing is the straight punch. The magnitude of force exerted at the point of impact is influenced by a number of factors. Therefore, some biomechanical parameters can have greater effect than others during punch performance. Likewise, different technique modalities influence punch force. This study aims to determine differences between kinetic and kinematic parameters of punches performed with two different techniques (with and without weight shifting).